The macroeconomic impact of IMF-supported programmes in small open economies : the case of Barbados - Boamah, Daniel ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Uses trend analysis along with the generalized evaluation estimator technique to assess the macroeconomic impacts of the IMF supported programmes on four target variables namely economic growth, inflation, the current account balance and the overall balance of the payment position.